Enhanced cycling stability of La0.2Sr0.8CoO3−δ for oxygen evolution reaction via trace doping of Nb. Issue 24 (15th December 2022) - Zhang, Chi; Cui, Yu; Ke, Wenxue; Liang, Yi; Chao, Yang; Han, Ning; Liang, Ping; He, Xin
Abstract: Perovskite oxides (ABO3−δ ) have highly tuneable compositions because of the abundance of element candidates for the A-, B-, and O-sites. Generally, perovskite catalytic activity for the oxygen evolution reaction (OER) can be improved by B-site doping. However, doping does not always enhance activity. This work shows that Nb doping of La0.2 Sr0.8 CoO3−δ (LSC) is detrimental to OER activity but benefits cycling stability. With 10 at.% Nb doping (La0.2 Sr0.8 Co0.9 Nb0.1 O3−δ, LSCN10), the overpotential at 10 mA cm −2 increased to 450 mV, 30 mV higher than that of the undoped LSC. Accelerated stability testing demonstrated enhanced stability with only 5 mV attenuation after 1000 cycles. Density functional theory (DFT) revealed that the high stability stems from the downward shift of the O 2 p band centre relative to the Fermi level. The findings of this work provide guidance for the design of highly stable OER perovskite catalysts.